Intoxication by Intraperitoneal Injection or Oral Gavage Equally Potentiates Postburn Organ Damage and Inflammation - Chen, Michael M.; Palmer, Jessica L.; Ippolito, Jill A.; Curtis, Brenda J.; Choudhry, Mashkoor A.; Kovacs, Elizabeth J. (Mediators of Inflammation, 2013)
The increasing prevalence of binge drinking and its association with trauma necessitate accurate animal models to examine the impact of intoxication on the response and outcome to injuries such as burn. While much research has focused on the effect of alcohol dose and duration on the subsequent inflammatory parameters following burn, little evidence exists on the effect of the route of alcohol administration. We examined the degree to which intoxication before burn injury causes systemic inflammation when ethanol is given by intraperitoneal (i.p.) injection or oral gavage. We found that intoxication potentiates postburn damage in the ileum, liver, and lungs of mice to an equivalent extent when either ethanol administration route is used. We also found a similar hematologic response and levels of circulating interleukin-6 (IL-6) when either ethanol paradigm achieved intoxication before burn. Furthermore, both i.p. and gavage resulted in similar blood alcohol concentrations at all time points tested. Overall, our data show an equal inflammatory response to burn injury when intoxication is achieved by either i.p. injection or oral gavage, suggesting that findings from studies using either ethanol paradigm are directly comparable.